The Effect of Leadership Empowerment, Psychological Capital, and Job Meaningfulness with Job Satisfaction as a Mediation Variable on the Performance of SOE Bank Employees in Makassar City - Zaeni, Nurhaeda; Mas’ud, Masdar; Gani, Achmad; ., Budiandriani; Mahmud, Amir (Journal of Ecohumanism, 2024)
This study aims to analyze the influence of Leadership Empowerment, Psychological Capital and Work Meaningfulness on performance mediated by Job Satisfaction. The research was conducted at a state-owned bank in Makassar City and involved 290 samples, The sample of this study was taken using the Hair Technique whose distribution was carried out proportionally. The data was analyzed using a Structural Equation Model (SEM) with the SmartPLS4 analysis tool. The results of the study prove that Leadership Empowerment has an effect on Performance, Psychological Capital has an effect on Performance, Work Meaningfulness has an effect on Performance, Leadership Empowerment has an effect on Job Satisfaction, Psychological Capital has no effect on Job Satisfaction, Work Meaningfulness has an effect on Job Satisfaction, Job Satisfaction has an effect on Performance, Leadership Empowerment has an effect on Performance through Job Satisfaction, Psychological Capital has no effect on Performance through Job Satisfaction, and Work Meaningfulness has an effect on Performance through Job Satisfaction. Job Satisfaction is able to mediate Leadership Empowerment and Work Meaningfulness and its implications for Performance improvement, but Job Satisfaction cannot mediate Psychological Capital in Performance improvement.